The frontiers of clinical research on transcranial direct current stimulation (tDCS) in Neuropsychiatry - Paulo S. Boggio (Frontiers Research Topics, 2015)
Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation intervention that induces changes in cortical activity and excitability according to the parameters of stimulation. TDCS effects have been reported since the 1800s with the development of the galvanic cell, although more systematic research has been conducted only from 1950-1970 and then from 1998 onwards. At the present time, most tDCS studies have been conducted in healthy volunteers, proving the properties of tDCS as a technique that induces long-lasting, polarity-dependent changes on specific brain areas. In addition, some studies have applied tDCS in selected neuropsychiatric samples, as to investigate its therapeutic effects, obtaining mixed albeit mostly positive results. Using tDCS in clinical practice could bring enormous gains for the treatment of several neuropsychiatric disorders, as tDCS is a portable, non-expensive and straightforward therapy, being therefore a putative candidate as an add-on or substitutive therapy for pharmacological treatments. However, there is still a gap between tDCS basic and clinical research, as it is still unknown whether and how the potent neuromodulatory effects observed after one tDCS session can be carried over for several weeks; therefore proving that tDCS is also a reliable clinical tool. In addition, another gap is observed in tDCS translational research, as results obtained from experimental animal models might not be fully generalizable to neuropsychiatric disorders in humans. Thus, advancing basic and experimental tDCS research as well as tailoring the optimal parameters of stimulation represents the frontiers of tDCS use in neuropsychiatry. In this special edition, our aim is to gather studies that contribute to the proposal of using tDCS for the treatment and investigation of neuropsychiatric disorders. Desired studies include (but are not limited to) the following topics: (1) clinical trials using tDCS as a treatment for neuropsychiatric disorders. (2) original studies investigating optimal parameters for daily tDCS stimulation. (3) safety and tolerability of tDCS, including reports of unexpected and serious adverse effects. (4) comprehensive reviews of putative mechanisms of action of tDCS for neuropsychiatric disorders. (5) translational research, testing different protocols of stimulation in experimental animals. (6) modeling tDCS studies, including studies testing different tDCS devices and montages. (7) studies of cost-efficacy analysis. (8) development of appropriate study designs for tDCS. (9) development of novel employments of tDCS, such as portable, safe devices that allow domestic utilization. (10) development of more precise and focal tDCS devices. To conclude, our ultimate aim is to host studies that contribute to bridge findings from basic and experimental tDCS research with clinical practice, therefore accelerating tDCS use as a novel arsenal for treating neuropsychiatric disorders.